Disperse of Ownership, Liquidity, and Firm Value: Evidence from Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to investigate the relationship between disperse of ownership, liquidity, and firm value using a sample of 225 Companies on Indonesia Stock Exchange (IDX) market conditions since 2014 until 2019. We examine disperse of ownership as measured by free float, liquidity as measured by Amihud illiquidity, firm value as measured by Tobin’s Q, and total assets, operating income to price ratio, financial leverage ratio, operating income on assets, relative bid-ask spread, turnover of stock, depth of stock, stock return, and return on assets as control variables. We use panel data, which is a combination of cross section and time series data from Thomson Reuters data stream. We find that this study indicated that free float is negatively associated with liquidity of stock and both firm value while liquidity of stock is positively associated with firm value. Our findings not only consistent with some prior research in relation to blockholder dispersion have a negative correlation with Tobin’s Q and disperse of ownership negatively impact liquidity of stock, but also can serve as a reminder for investor that liquid stock may not provide positive returns.